2008
DOI: 10.1002/crat.200800010
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic behavior of Zn1−xMnxO at room temperature

Abstract: Mn-doped ZnO were synthesized by solid state reaction and sol-gel method respectively. It was found that samples synthesized by solid state reaction containing Mn 2 O 3 and MnO 2 are a mixture of ferromagnetic and paramagnetic phases. Contrary, samples without second phases were found to be paramagnetic at room temperature. According to previous report, interface effects between Zn-rich Mn 2 O 3 and MnO 2 interfaces may be the origin of the ferromagnetic behavior observed in our samples prepared by solid react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…In fact, room temperature ferromagnetism (RTFM) has been reported for ZnO-Mn [5] and ZnO-Co [6] systems. In contrast, Yang et al [7] believe that the magnetism of Zn 1−x Mn x O is paramagnetic at room temperature. The conflicting results have led to the growing interest in both theoretical [4] and experimental [8] studies on transition-metal (TM) doped ZnO.…”
Section: Introductionmentioning
confidence: 92%
“…In fact, room temperature ferromagnetism (RTFM) has been reported for ZnO-Mn [5] and ZnO-Co [6] systems. In contrast, Yang et al [7] believe that the magnetism of Zn 1−x Mn x O is paramagnetic at room temperature. The conflicting results have led to the growing interest in both theoretical [4] and experimental [8] studies on transition-metal (TM) doped ZnO.…”
Section: Introductionmentioning
confidence: 92%
“…In spite of numerous studies the ferromagnetic properties of transition metal cations doped wurtzite ZnO host is still a controversial issue [1][2][3][4][5][6]. A high temperature ferromagnetism was reported numerously for Co doped ZnO in thin films produced by all accessible methods including pulsed layer deposition [7], the magnetron co-sputtering [8], the solgel method [9], and epitaxial thin films [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gu et al 20 found RTFM in sol–gel synthezied Zn 0.95 Co 0.05 O, and enhanced RTFM in SiO 2 treated and carbon nanotubes treated Zn 0.95 Co 0.05 O, however attributed it to the interfacial oxygen deficiency and tunable by changing the oxygen vacancies. On the other hand, Yang et al 21 reported room temperature paramagnetic behavior in Mn doped ZnO synthesized by sol–gel method using citric acid. All these experimental results have opened a still more challenging debate as to the origin of ferromagnetic behavior in TM ions doped ZnO nanocrystalline systems.…”
Section: Introductionmentioning
confidence: 99%